The Role of The Press In The Upbringing of The Personal Composition of Border Troops In Uzbekistan In The Spirit of Patriotism - Nuralievich, Shaymardanov (Pubmedia Social Sciences and Humanities, 2025)
This article explores the role of the press in fostering patriotism among the military personnel of Uzbekistan’s border troops during the years of independence. It delves into how the press contributes to cultivating loyalty to the homeland, courage, valor, perseverance, and other noble qualities. Additionally, the article examines the military-patriotic ideology, socio-political, spiritual, educational, and philosophical dimensions of patriotism, highlighting the state significance of this educational effort and its moral and ethical foundations.